Aplikasi Market Matching Berbasis Fuzzy sebagai Penunjang Keputusan Ekspor Produk UMKM - Nurdewanto, Bambang (Department of Informatics Engineering, 2017)
Determining the exact location of the export market with the right amount in the marketing process is expected to reduce the number of losses due to the stagnancy of product turnover. Appropriate target market system using fuzzy control on MSMEs. Fuzzy control method is used to overcome the determination of a market that is influenced by the subjectivity of marketing actors. Online market matching application which is the right decision support system of the right export destination and the right amount so efficient. The result of market matching application of fuzzy method is recommendation of destination and quantity that can be exported.